Relationship between hip strength and trunk motion in college cross-country runners - Ford, K. R.; Taylor-Haas, J. A.; Genthe, K.; Hugentobler, J. (Medicine & Science in Sports & Exercise, 2013)
Purpose: Hip strength may directly relate to abnormal running mechanics and contribute to the high incidence of overuse injuries in distance runners. The purpose of this study was to determine the relationship between hip isokinetic strength and thorax and pelvic motion during treadmill running.